Проблема надійності водопровідних мереж на прикладі міста Кропивницького - Клименко, В. В.; Ковальчук, Н. В.; Гуцул, В. І.; Телюта, Р. В.; Klymenko, V.; Kovalchuk, N.; Hutsul, V.; Teliuta, R. (ЦНТУ, 2021)
В статті проаналізовано причини аварій та витоків на водопровідних трубах розподільчої мережі м. Кропивницького та обраховано статистичні дані експлуатаційної організації по аварійним ситуаціям при експлуатації трубопроводів діаметром від 25 до 1100 мм протягом останніх п’яти років. Встановлено, що основними видами пошкоджень труб водопровідної мережі є : наскрізні свищі сталевих труб – 54,4%; корозія сталевих труб – 25,6%; розчеканка стиків чавунних труб – 9,7%, переломи та тріщини чавунних труб – 6,1%; тріщини на стиках пластикових труб та інші – 4,2%. Отримано аналітичні залежності середнього значення параметра потоку відмов трубопроводу ω0ср від діаметра труб D та підтверджено тенденцію зменшення ω0ср при збільшенні D. Рекомендовано для підвищення надійності водопровідних мереж проводити заміну 2% мережі на рік та використовувати пластикові труби. Для зменшення ω0ср, зокрема на ділянках труб з понаднормовим терміном експлуатації, показана доцільність установлення парціально безпосередньо в трубопровід водоповітряних гасників коливань тиску, в яких відбувається поступове і повне гасіння ударної хвилі. The article presents the analysis of statistical data of the causes of breakages and leaks in water pipes of the distribution network of Kropyvnytskyi. Breakage statistics for pipelines with a diameter of 25 to 1100 mm during the last five years were calculated. As a result of segmental analysis, it was found that the main types of damage to the pipes of water supply system are through fistulas of steel pipes – 54.4% and corrosion – 25.6%; loss of integrity of cast iron pipes on joints – 9.7%, fractures and cracks of cast iron pipes – 6.1%; fractures in joints of polyethylene pipes and other damages – 4.2%. To characterize the reliability of the municipal water supply networks, the pipeline failure flow parameter ω was used. It was defined as the ratio of the number of failures of the water supply network section to the observation period and the length of pipe network sections of the corresponding diameter. The calculation of interval estimates for the failure rate parameter ωо for steel and cast iron pipes of the water distribution network of Kropyvnytskyi was carried out. According to the operational organization 84% of the network was laid using these pipes and analytical expressions were obtained to determine average values of ω0ср depending on their diameter. Significantly higher values of ω0ср were noted in comparison with similar ones given in the literature for other cities, which can be explained by a significant excess of the standard service life of 85% of steel and 50% of cast iron pipes in the water supply network of Kropyvnytskyi. To increase the reliability of water supply networks, it is recommended to implement the experience of European countries and replace 2% of the network per year and use polyethylene pipes. To reduce the failure factor of water supply networks, particularly in those areas where overtime pipes are used, the expediency of partial installation of water-air dampers for pressure fluctuations directly in the pipeline, in which there is a gradual and complete damping of the shock wave. Approbation of a prototype of a hydraulic shock absorber of this design was carried out in the hydraulics laboratory at Central Ukrainian National Technical University and its efficiency and high efficiency at full shock wave damping was confirmed.
The Problem of Reliability of Water Supply Networks on the Example of the City of Kropyvnytskyi
Keywords: водопровідна мережа; труби; аварії; надійність; потік відмов; breakages; steel pipelines; distribution network; reliability; failure